Isolation and Identification of Lactobacillus Bacteria from Culled Hens Meat for Meat Biopreservator - Lengkey, Hendronoto Arnoldus W.; Balia, Roostita Lobo; Siwi, Jan Alex; Tasbac, Bogdan A.; Togoe, Iulian (KnE Life Sciences, 2017)
Using chemical bio-preservatives is being frowned at because of their probable adverse effects on the health of consumers. Isolation and identification of microorganisms from natural resources are an occurring process that have most powerful means for obtaining cultures and also have commercial purposes. The aim of this study was to get bio-preservatives from poultry meat, by isolation and then identification of lactic acid bacteria. Lactic acid bacteria do not pose any health risks to human, and are generally recognized as safe (GRAS) organisms. The lactobacillus were isolated from raw poultry meat by appropriate dilutions with NaCl fisiological, and the decimal dilution were mixed with MRS medium and then incubated at 370C for 48-72 h. Pure cultures were maintained in MRS broth agar at 40C for short term use. Thirty well-isolated colonies were picked up and transferred to MRS broth. Selection of strains was made in agreement with morphology, Gram-stain, viability during storage at 40C and antimicrobial activity, was found twenty isolate. The identification of the cultures was based on the characteristics of the lactobacilli as described in Bergey’s manual of determinative bacteriology, fermentation of different carbon sources, gas production from glucose, growth at different temperatures. For anti-biogram, the isolates were inoculated into MRS broth individually and incubated for 24h. The plates were incubated at 37oC overnight. Resistance was defined as the absence of a growth inhibition zone around the discs. Results indicated that 20 isolate of Lactic acid bacteria were identified: 3 isolates of Lactobacillus fermentum, 2 isolates of Lactobacillus paracasei ssp. paracasei, 5 isolates of Lactobacillus plantarum, 3 isolates of Lactobacillus rhamnosus, 2 isolates of Lactobacillus lactis ssp. lactis 1, and 5 isolates of Lactobacillus lactis ssp. lactis 2. Characterization of the microbial metabolic product for antimicrobial agents reveals that lactic acid bacteria has responsibility for the inhibition of the indicator organisms, and can be used as meat biopreservator. Keywords: isolation, identification, lactobacillus, poultry meat, biopreservator.